Magnetic compression anastomosis for biliojejunostomy and pancreaticojejunostomy in Whipple's procedure: An initial clinical study. Issue 3 (19th October 2018) - Liu, Xue‐Min; Li, Yu; Xiang, Jun‐Xi; Ma, Feng; Lu, Qiang; Guo, Yan‐Guang; Yan, Xiao‐Peng; Wang, Bo; Zhang, Xu‐Feng; Lv, Yi
Abstract: Background and Aim: Magnetic anastomosis has been attempted in biliary and intestinal reconstruction. The objective of the current study was to introduce an initial clinical use of magnetic compression anastomosis for pancreaticojejunostomy and biliojejunostomy in Whipple's procedure. Methods: Patients with peri‐ampullary carcinoma and dilated bile and pancreatic ducts were prospectively enrolled from 2016 to 2017. After pancreaticoduodenectomy, an appropriate mother magnet and drainage tube was placed in the proximal bile duct and pancreatic duct. The daughter magnets were introduced to mate with the mother magnets at the anastomotic sites. A close postoperative surveillance and routine cholangiopancreaticography via the drainage tube were performed. Results: One female and three male patients with a median age of 69 years (range, 57–77) were included. The diameter of the common bile ducts and pancreatic ducts ranged from 8 to 15 mm, and 7 to 10 mm, respectively. The median time duration for biliojejunostomy and pancreaticojejunostomy was 7 (range, 5–8 min) min and 9 (range, 8–10 min) min, respectively. The median time of biliojejunostomy and pancreaticojejunostomy formation was 17 (range, 15–21 days) days and 11 (range, 10–18 days), respectively. With a median follow up of 313 days, one patient developed biliary anastomotic stricture at 11 months after surgery, and underwent stent placement via percutaneous transhepatic drainage sinus, and recovered well. Conclusions: Magnetic anastomosis is safe, effective, and simple for both biliojejunostomy and pancreaticojejunostomy in Whipple's procedure.